Responsibility in Existential Approach of Psychotherapy - Gralak, Anita (Folia Philosophica, 2016)
The aim of this paper is to show that responsibility arises from an existential dimension of human being and, therefore an existential depth is a necessary condition of undertaking or rejecting responsibility. Linking ethical and existential dimensions has an application in a process of psychotherapy, beginning from M. Boss, to I.D. Yalom. Both of them applied the philosophical issues of M. Heidegger’s thought. Yalom isolated the area of problems and medical conditions, and put forward a thesis that they arise from the existential depth of Dasein, and thus assuming or escaping responsibility brings consequences for mental health. Following such indications one may find himself on a ground of his own responsibility. In this paper, it will be shown that if one deals with existential issues, one may answer to human problems during the process of psychotherapy, and might approximate himself to authenticity, which means prosperity, well-being and integration of personality. I hope that the following paper will be a contribution to polemics and a treatment among milieu of philosophers, but not only among psychotherapists. key words: existentialism, responsibility, psychotherapy, yalom, heidegger